Open market repurchases and firm stock return variation: evidence in Malaysia stock market - Chee, Chong Meng; Ab Razak, Nazrul Hisyam (Panoply Consultancy, 2017)
The main research objective of this research paper is to examine the effect of private information, which is extracted from stock price, on firm's open market repurchases (OMRs) activity. The finding of study is to provide evidence of presence of managerial market-timing of repurchases whereby managers could use variation of firm stock return to time open market repurchase. Evidence is however found only in the subsample analysis where target sample is separated to two subsamples periods and test separately based on stock market performance. The finding of the 1st subsample (Q12008-Q42013) for OMRs activity indicates that variation of stock return and firm size significantly and positively explains OMRs activity. The finding of 1st subsample is robust in terms of random and fixed effect model. It indicates that managers should observe and learn from firm-specific variation in stock return during financial crisis and recovery periods when performing open market repurchases. In line with past empirical findings, firm leverage and free cash flow are not significant. The result of the 2nd subsample (Q12014-Q42015) for OMRs activity shows that variation of firm's stock return is no useful for managers to time repurchase. Both findings may indicate that managers would have more chances in timing repurchase during market downtime.